DETERMINASI KEPATUHAN MINUM OBAT PADA PASIEN DIABETES MELLITUS TIPE II DI PUSKESMAS TERARA: ANALISIS KORELASI FAKTOR-FAKTOR PENGARUH - Sovia, Fitriwati; Anjani, Rizky Puji; Ramadhan, Leny (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2024)
Diabetes mellitus is a chronic disease that requires ongoing management because it cannot be permanently cured. Adherence to the treatment plan is crucial to prevent deterioration in physical condition. This study aims to analyze the correlation between factors affecting medication adherence in patients with type II diabetes mellitus at Terara Community Health Center. This research uses an observational analytic design with a cross-sectional approach. The study population consists of 151 patients with type II diabetes mellitus, with a sample of 35 individuals selected through purposive sampling. Data were collected using a questionnaire and analyzed with Fisher's test. The results indicate that factors such as gender (P=0.015), occupation (P=0.015), knowledge (P=0.006), attitude (P=0.001), motivation (P=0.021), and family support (P=0.004) have a significant correlation with medication adherence. Conversely, age, education, and healthcare support did not show a significant correlation with medication adherence. In conclusion, factors such as gender, occupation, knowledge, attitude, motivation, and family support significantly influence medication adherence in patients with type II diabetes mellitus at Terara Community Health Center.